The Effect of Islamic Service Quality and Mobile Banking Features on Customer Loyalty with Satisfaction as an Intervening Variable: A Study of Customers of NTB Syariah Bank - Kistiqul Aprilianti; Sanurdi Sanurdi (STKIP Taman Siswa Bima, 2025)
The objective of this research was to analyze the influence of Islamic service quality and mobile banking features on customers’ loyalty with satisfaction as an intervening variable (study on the customers of Bank NTB Syariah). This research was conducted at Bank NTB Syariah which is located at Jl. Udayana, Dasan Agung Mataram NTB. The background of this research was based on the growth and development of banks based on sharia so that they experienced fierce competition, especially in the service quality based on sharia, along with the technology development, Islamic banks also have services in the form of sharia mobile banking, with various features on it. The research method used in this research was quantitative method. The data collection technique used questionnaire distributed to the customers of Bank NTB Syariah consisting of 96 customers who have mobile banking and have made at least 3 transactions. Data analysis was carried out by using SPPS 21 to test the validity, reliability, and significance among variables. The results of this research showed that Islamic service quality and mobile banking features of Bank NTB Syariah had significant influences on the customers’ loyalty and customers’ satisfaction. Customers’ loyalty had significant influences on the customers’ satisfaction and Islamic service quality and mobile banking features influenced customers’ loyalty through customers’ satisfaction as an intervening variable.